Explanation:
y = Ix-2I - 1
when x = -5
y = I(-5)-2I - 1
y = I-7I - 1
y = 7 - 1
y = 6
___________________________
when x = -3
y = I(-3)-2I - 1
y = I-5I - 1
y = 5 - 1
y = 4
___________________________
when x = -1
y = I(-1)-2I - 1
y = I-3I - 1
y = 3 - 1
y = 2
___________________________
when x = 0
y = I(0)-2I - 1
y = I-2I - 1
y = 2 - 1
y = 1
___________________________
when x = 1
y = I(1)-2I - 1
y = I-1I - 1
y = 1 - 1
y = 0
___________________________
when x = 3
y = I(3)-2I - 1
y = I1I - 1
y = 1 - 1
y = 0
___________________________
when x = 5
y = I(5)-2I - 1
y = I3I - 1
y = 3 - 1
y = 2